2016
DOI: 10.1136/bjsports-2015-095739
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise selection on hamstring muscle activation

Abstract: We highlight the heterogeneity of hamstring activation patterns in different tasks. Hip-extension exercise selectively activates the long hamstrings, and the Nordic exercise preferentially recruits the semitendinosus. These findings have implications for strategies to prevent hamstring injury as well as potentially for clinicians targeting specific hamstring components for treatment (mechanotherapy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 55 publications
11
114
2
6
Order By: Relevance
“…However, it can be argued that such metabolic changes are secondary to reduced muscle activation. Finally, while there was no control group (without a history of ACLR) in this study, the activation patterns of the uninjured control limbs are very similar to those that have been observed in healthy uninjured limbs (Bourne et al, 2016;Bourne, Williams, et al, 2017;Messer, Bourne, Williams, & Shield, 2017). …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, it can be argued that such metabolic changes are secondary to reduced muscle activation. Finally, while there was no control group (without a history of ACLR) in this study, the activation patterns of the uninjured control limbs are very similar to those that have been observed in healthy uninjured limbs (Bourne et al, 2016;Bourne, Williams, et al, 2017;Messer, Bourne, Williams, & Shield, 2017). …”
Section: Discussionsupporting
confidence: 72%
“…The present findings of relatively low levels of post-surgical ST activation in the demanding NHE also suggest that this muscle receives a limited stimulus for adaptation, even during a supramaximal exercise which is known to preferentially target this muscle (Bourne, Duhig, et al, 2017;Bourne, Williams, et al, 2017).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We recently showed that the long hamstrings, including the BFLH, are relatively more evenly activated during a hip extension exercise than in the NHE1 and this suggests the possibility that the latter may be more effective at increasing BFLH muscle size. This may be important in rehabilitation given the observation of persistent BFLH atrophy after strain injury 8…”
mentioning
confidence: 99%
“…However, it has been argued that the NHEs may be suboptimal for injury prevention because it involves preferential activation of the semitendinosus and biceps femoris short head muscles 1. It has also been proposed that exercise at longer muscle lengths than those observed in the NHE may be more effective at increasing BFLH fascicle length,6 an apparent risk factor for hamstring injury 7…”
mentioning
confidence: 99%